The origins of the Platonic Academy of Florence - Field, Arthur, 1948- (Princeton legacy library, 1988)
Founded by Cosimo de' Medici in the early 1460s, the Platonic Academy shaped the literary and artistic culture of Florence in the later Renaissance and influenced science, religion, art, and literature throughout Europe in the early modern period. This major study of the Academy's beginnings presents a fresh view of the intellectual and cultural life of Florence from the Peace of Lodi of 1454 to the death of Cosimo a decade later. Challenging commonly held assumptions about the period, Arthur Field insists that the Academy was not a hothouse plant, grown and kept alive by the Medici in the splendid isolation of their villas and courts. Rather, Florentine intellectuals seized on the Platonic truths and propagated them in the heart of Florence, creating for the Medici and other Florentines a new ideology. Based largely on new or neglected manuscript sources, this book includes discussions of the earliest works by the head of the Academy, Marsilio Ficino, and the first public, Platonizing lectures of the humanist and poet Cristoforo Landino. The author also examines the contributions both of religious orders and of the Byzantines to the Neoplatonic revival. Originally published in 1988. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.